(untitled) (Research, Society and Development, 2023)
Introduction: Breastfeeding is the most appropriate means of feeding to provide the growth and development of the child’s structures and functions, such as breathing, sucking, swallowing, chewing and speaking. Currently, there are several campaigns encouraging exclusive breastfeeding, which seek to support mothers throughout this process. However, the numbers still point to a large number of children who suffer from early weaning. This study aims to describe speech therapy in maternity wards and how speech therapy can be more valued in the context of breastfeeding. Methods: Through an integrative review of the literature, this study analyzed the scientific production on speech therapy during breastfeeding in maternity hospitals, of articles in Portuguese, published between 2018 and 2023. Results and Discussion: Of the 9 articles included in this research, it was unanimously addressed: breastfeeding and speech therapy. Furthermore, factors that influence breastfeeding were also presented in all works. Studies highlight how much postpartum women and newborns tend to gain from the perspective of a qualified professional, when faced with issues of orofacial disorders and human communication, making approaches more specialized and humanized. Conclusion: The present study described speech therapy work in maternity hospitals, with the professional being trained to disseminate information regarding the benefits of breastfeeding, promote greater bonding between the mother-newborn dyad, evaluate breastfeeding and sucking pattern and avoid early weaning . Regarding the valorization of speech therapy work in the context of breastfeeding, a lack of clear and relevant exposure to speech therapy work was observed, strengthening and reinforcing the need for actions that promote an environment and individual moment to address issues about breastfeeding mother and how the speech therapist should be inserted in this scenario.